Threshold regression analysis of public education spending policy on economic growth in Lebanon - Zabad, Hussein; Taher, Hanadi (Edelweiss Applied Science and Technology, 2025)
This research investigates the nonlinear effect of public education spending on economic growth in Lebanon and tests for threshold effects that can change this relationship. We use annual time-series data from 1993 to 2023 and employ threshold regression analysis following Hansen's procedure, as well as the Autoregressive Distributed Lag (ARDL) approach. The determinants in the analysis are Gross Domestic Product per capita (GDPPC), education expenditure (EDUCEXP), secondary school enrollment (ENROL), total labor force (TLF), and fixed capital formation (FBCF). The Hansen test indicates a statistically significant threshold effect. Below the identified threshold, education expenditure has no significant impact on economic growth. However, expenditure above the threshold shows a strong negative correlation with economic growth (coefficient: -0.466, p-value: 0.044). The ARDL bounds test confirms the absence of long-run cointegration between the variables. The relationship between economic development and education spending in Lebanon is nonlinear and depends on the level of expenditure. The findings oppose traditional linear hypotheses and show that excessive spending at high levels is harmful. Policymakers should focus on enhancing the productivity of education expenditure instead of increasing the budget. Inefficiencies in the structure must be addressed, institutional standards increased, corruption addressed, and educational output aligned with labor market demand so that the productivity of education investment in Lebanon is enhanced.